IKRAR TALAK PENYANDANG TUNAWICARA DALAM MAZHAB HANAFI DAN MAZHAB SYAFI'I - Arofik, Slamet; Rifa'i, Ahmad (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
The problem arises when a husband who is a mute wants to divorce his wife. How do scholars respond to this issue? This research uses a qualitative approach with a type of library research, generating theory rather than hypothesis testing, so the resulting theory is in the form of a substantive theory. The results of the study show that the divorce oath for a mute person according to the Hanafi School of Thought can use gestures with the condition that he is unable to write, because gestures are below the level of writing. Meanwhile, according to the Shafi'i School of Thought, the divorce oath for a mute person can be conveyed by writing or gestures absolutely, because both are considered equal. The difference of opinion between the Hanafi and Shafi'i schools of thought lies in the legalization of divorce with gestures, namely in the Hanafi School of Thought there is a condition if he is unable to write and based on the method of istinbāṭ istihsan. Whereas in the Shafi'i School of Thought, the permissibility of divorce using gestures absolutely can be based on the method of Qiyas. The similarity is that both use the Qur'an and Hadith as the first and second sources of law before others. The next similarity is that both agree that divorce can be conveyed by writing or gestures.